2020
DOI: 10.1038/s41467-020-14595-4
|View full text |Cite
|
Sign up to set email alerts
|

H3K4 methylation at active genes mitigates transcription-replication conflicts during replication stress

Abstract: Transcription-replication conflicts (TRCs) occur when intensive transcriptional activity compromises replication fork stability, potentially leading to gene mutations. Transcriptiondeposited H3K4 methylation (H3K4me) is associated with regions that are susceptible to TRCs; however, the interplay between H3K4me and TRCs is unknown. Here we show that H3K4me aggravates TRC-induced replication failure in checkpoint-defective cells, and the presence of methylated H3K4 slows down ongoing replication. Both S-phase ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 91 publications
2
42
0
Order By: Relevance
“…This provides an opportunity for mutation rates to evolve in beneficial directions (e.g., lower mutation rates in cytogenetic states characteristic of essential housekeeping genes where mutations are more likely to be deleterious). Indeed, processes facilitating reduced mutation rates in genic regions 22,29,33 and active genes 15,17,21,24,34 have already been documented in recent years. These discoveries are consistent with contemporary theoretical predictions from population genetics that beneficial mutation rates could readily evolve even in the face of genetic drift if mutation rates are linked to gene regulation or common sequence and epigenomic features 3,8 .…”
Section: Classical Evolutionary Theory Maintains That Mutation Rate Vmentioning
confidence: 99%
See 2 more Smart Citations
“…This provides an opportunity for mutation rates to evolve in beneficial directions (e.g., lower mutation rates in cytogenetic states characteristic of essential housekeeping genes where mutations are more likely to be deleterious). Indeed, processes facilitating reduced mutation rates in genic regions 22,29,33 and active genes 15,17,21,24,34 have already been documented in recent years. These discoveries are consistent with contemporary theoretical predictions from population genetics that beneficial mutation rates could readily evolve even in the face of genetic drift if mutation rates are linked to gene regulation or common sequence and epigenomic features 3,8 .…”
Section: Classical Evolutionary Theory Maintains That Mutation Rate Vmentioning
confidence: 99%
“…The observed negative correlation between GC content and mutation rate was consistent with other observations of lower mutation rate in GC rich regions 23,[39][40][41][42] and mechanistically with both GC biased gene conversion 43 and lower rates of cytosine deamination in GC rich regions 10,[44][45][46][47] . Furthermore, the histone modifications H3K4me1 and H3K27ac are known to be associated with lower mutation rates, particularly in active genes 21,[48][49][50] , and several studies have revealed explicit connections between H3K36me3 and DNA mismatch repair 13,16,17 . These chromatin marks were enriched in gene bodies (Fig.…”
Section: Classical Evolutionary Theory Maintains That Mutation Rate Vmentioning
confidence: 99%
See 1 more Smart Citation
“…The slower recovery of set1Δ from HU exposure is not the consequence of a defect in origin initiation but most likely in the processing of HU-stalled forks. Second, Set1 has a role in protecting the genome from TRCs occurrence with the transcription-deposited H3K4 methylation decelerating the fork progression at highly transcribed regions [32].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the DNA damage checkpoint acts together with the spindle assembly checkpoint to restrict the growth of orc5-1 set1Δ cells. Because orc5-1 set1Δ viability is decreased by the lack of RNase H activity but rescued by the reduction of histone gene dosage, we propose that the role Set1 plays in TRCs limitation [32] becomes critical when replication fork velocity is increased due to the orc5-1 mutation. On another hand, orc5-1 set1Δ cell death is partly the consequence of reactive oxygen species (ROS) accumulation, likely in response to DNA damage.…”
Section: Introductionmentioning
confidence: 99%